Polskie gospodarstwa warzywnicze na tle wybranych krajów Unii Europejskiej - Ziętara, Wojciech; Sobierajewska, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
The article indicated the role of vegetable production in Polish agriculture. They provide better use of the land, due to the higher its productivity. Polish farms were evaluated comparing to similar vegetable farms in Hungary, Germany and the Netherlands. It has been shown that Polish vegetable farms of the economic size between 40 and 100 ESU and above 100 ESU are competitive compared to farms in other countries and are able to develop. Dutch and German farms of similar economic size classes have limited development opportunities.